LUBAC and NF‐κB trigger a nuclear response from mitochondria. (18th November 2022) - Chen, Junsheng; Simmen, Thomas
Abstract : Mitochondria are key signaling hubs for innate immune responses. In this issue, Wu et al (2022) report that remodeling of the outer mitochondrial membrane by the linear ubiquiting chain assembly complex (LUBAC) facilitates transport of activated NF‐κB to the nucleus in response to TNF signaling. Abstract : Mitochondria and linear ubiquitination take prime position in promoting nuclear translocation of activated NF‐kB.